2013
DOI: 10.1080/09540121.2013.774314
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of frequency of HIV testing among men who have sex with men in Washington, DC

Abstract: In Washington, DC, the leading mode of HIV transmission is through men who have sex with men (MSM) behavior. This study explored differences between frequent HIV testers (men testing at least twice a year) and annual or less frequent testers (men testing once a year or less) in DC. Nearly, one-third of MSM reported testing for HIV at least four times in the prior two years. In the multivariable model, frequent testers had significantly higher odds of being aged 18-34 (aOR =1.94), knowing their last partner's H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…Overall, these results highlight the importance of primary HIV prevention that emphasizes both the HIV risk inherent even in infrequent or rare risk behavior, as well as the importance of frequent, routine HIV testing, regardless of perceived risk. [40][41][42] Results from this study also show that unemployed MSM were significantly less likely to be recently tested for HIV, even after controlling for whether they engaged in risky sexual behavior. Importantly, income was not associated with recent HIV testing, and the ''employed'' group included individuals who were full-time students, suggesting that the observed association is not being driven by access to financial resources alone.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Overall, these results highlight the importance of primary HIV prevention that emphasizes both the HIV risk inherent even in infrequent or rare risk behavior, as well as the importance of frequent, routine HIV testing, regardless of perceived risk. [40][41][42] Results from this study also show that unemployed MSM were significantly less likely to be recently tested for HIV, even after controlling for whether they engaged in risky sexual behavior. Importantly, income was not associated with recent HIV testing, and the ''employed'' group included individuals who were full-time students, suggesting that the observed association is not being driven by access to financial resources alone.…”
Section: Discussionsupporting
confidence: 53%
“…35 In a study providing HIV testing in bathhouses, Mayer reported that two-thirds of the MSM who engaged in UAI in the 2 months prior to HIV testing considered their HIV risk to be low, 43 suggesting that some MSM inaccurately assess the risk associated with their behavior. On the other hand, studies consistently demonstrate that MSM who test frequently also engage in more risky sexual behavior, such as having multiple sexual partners 42,44,45 and unprotected anal sex. 37,38,45,46 As a result, when diagnosed, these men are more likely to be acutely infected with HIV, when the likelihood of HIV transmission is significantly increased, 47,48 likely due to a spike in viral load levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The low rate of regular HIV testing among the MSM was consistent with other reports from Asia (Chow, Wilson, & Zhang, 2012;Li et al, 2012). MSM with HIV-positive tests were less likely to test regularly than those found HIV-negative (Phillips et al, 2013). MSM who accessed mobile clinic HIV testing services were less interested in regular HIV testing and immediate ART than those at TRCAC (p = 0.005 and p = 0.001, respectively).…”
Section: Discussionsupporting
confidence: 91%
“…19,22 Research on partnership status is equivocal; some studies suggest that MSM in a primary main partnership are more likely to test, 19,23 whereas others find the opposite. 24 In addition to understanding these demographic and behavioral factors, efforts to increase regular HIV testing among MSM can be informed by theory and research from social and health psychology regarding the impact of perceived stigma on health behaviors. 25 Research suggests that individuals sometimes act in ways that undermine their objective selfinterest in order to reduce their association with a stigmatized condition.…”
mentioning
confidence: 99%